Jak badać libertariańską teorię sprawiedliwości? Uwagi metodologiczne na temat struktury, problemów i metod badania teorii dedukcyjnej - Dominiak, Łukasz (Dialogi Polityczne, 2018)
In the present essay we share our ideas concerning methods by which the libertarian theory of justice should, in our opinion, be investigated. First of all, we classify libertarianism as a deductive theory that derives all its statements from the first principles of justice: the self-ownership principle, the homestead principle and the principle of voluntariness in transfer. We distinguish two modes of inquiry that should be employed with regard to the libertarian theory: conceptual and substantive investigations. In the first area the Hohfeldian analysis of the fundamental jural conceptions proves to be highly illuminating. In the second area the traditional philosophical investigations, thought experiments and transcendental inquiries promise to yield good results.